Sistem Monitoring IoT untuk Evaluasi Kebersihan Alat Konverter pada Insinerator Sampah - Zumhari Zumhari; Yuvina Yuvina; Fera Damayanti; Tuti Adi Tama Nasution; Mardiana Mardiana (Universitas Harapan Medan, 2026)
The issue of waste in major cities is one of the biggest challenges that needs to be addressed. To tackle this, an Internet of Things (IoT)-based clean urban system is designed to reduce waste volume, improve environmental quality, and generate renewable electricity. The method used consists of several main components. First, smart bins equipped with sensors identify the amount and type of waste, with data sent to an IoT platform for analysis. Second, an incinerator is used to burn waste and produce thermal energy, which is then converted into electrical energy by a thermoelectric generator. Third, the IoT platform manages data from thermocouple and MQ-2 sensors to monitor the combustion process and air quality. This platform also provides system performance information to users. The implementation of this system is expected to significantly reduce urban waste volume, enhance environmental quality, and generate renewable energy. Furthermore, this system has the potential to improve waste management efficiency and public awareness.